2015
DOI: 10.1098/rspa.2014.0746
|View full text |Cite
|
Sign up to set email alerts
|

‘Parabolic’ trapped modes and steered Dirac cones in platonic crystals

Abstract: This paper discusses the properties of flexural waves governed by the biharmonic operator, and propagating in a thin plate pinned at doubly periodic sets of points. The emphases are on the design of dispersion surfaces having the Dirac cone topology, and on the related topic of trapped modes in plates for a finite set (cluster) of pinned points. The Dirac cone topologies we exhibit have at least two cones touching at a point in the reciprocal lattice, augmented by another band passing through the point. We sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…These striking features of the scattering pattern around the double grating in an elastic flexural plate are also linked to the earlier paper [6], which addressed dispersion properties and directional localisation of Bloch-Floquet waves in infinite periodic structures.…”
Section: Blockage or Waveguiding By The Double Gratingsupporting
confidence: 57%
See 4 more Smart Citations
“…These striking features of the scattering pattern around the double grating in an elastic flexural plate are also linked to the earlier paper [6], which addressed dispersion properties and directional localisation of Bloch-Floquet waves in infinite periodic structures.…”
Section: Blockage or Waveguiding By The Double Gratingsupporting
confidence: 57%
“…It is also relevant to cite [6] where degeneracies were analysed in the structure of the dispersion surfaces in connection to flexural waves in 'platonic crystals' built with a doubly periodic rectangular array of rigid pins. It was also found that the relative spacings in the vertical and horizontal directions are important in order to control the order of degeneracy of multiple roots of the dispersion equation.…”
Section: An Algebraic System For the Source Intensitiesmentioning
confidence: 99%
See 3 more Smart Citations